Unraveling the Antimicrobial Effectiveness of Coridothymus capitatus Hydrolate against Listeria monocytogenes in Environmental Conditions Encountered in Foods: An In Vitro Study - Francesco Buccioni; Chiara Purgatorio; Francesca Maggio; Stefania Garzoli; Chiara Rossi; Luca Valbonetti; Antonello Paparella; Annalisa Serio (Microorganisms, 2022)
The increased resistance of bacteria to antimicrobials, as well as the growing interest in innovative and sustainable alternatives to traditional food additives, are driving research towards the use of natural food preservatives. Among these, hydrolates (HYs) have gained attention as “mild” alternatives to conventional antimicrobial compounds. In this study, the response of L. monocytogenes ATCC 7644 exposed to increasing concentrations of Coridothymus capitatus HY (CHY) for 1 h at 37 °C was evaluated by means of Phenotype Microarray, modelling the kinetic data obtained by inoculating control and treated cells into GEN III microplates, after CHY removal. The results revealed differences concerning the growth dynamics in environmental conditions commonly encountered in food processing environments (different carbon sources, pH 6.0, pH 5.0, 1–8% NaCl). More specifically, for treated cells, the lag phase was extended, the growth rate was slowed down and, in most cases, the maximum concentration was diminished, suggesting the persistence of stress even after CHY removal. Confocal Laser Scanner Microscopy evidenced a diffuse aggregation and suffering of the treated cells, as a response to the stress encountered. In conclusion, the treatment with HY caused a stressing effect that persisted after its removal. The results suggest the potential of CHY application to control L. monocytogenes in food environments.